2015
DOI: 10.1093/humupd/dmv057
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and its potential interest in assisted reproduction cycles

Abstract: Leptin regulates energy balance and female reproductive function, mainly through its action on hypothalamic-pituitary-ovarian function, whose molecular and cellular aspects are progressively being deciphered. Preliminary studies evaluating leptin as a biomarker in human IVF seem promising but need further confirmation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 138 publications
1
38
0
2
Order By: Relevance
“…The potential pharmacological use of leptin to improve or reduce the impact on obese male fertility has been already suggested and although their potential use in clinical practice is promising, the data are still limited and need further confirmation (Alves et al ., ). Interestingly, previous studies suggested also the potential clinical use of leptin as a biomarker in IVF cycles, considering that high serum and/or follicular fluid leptin concentrations have correlated negatively with cycle outcome (Catteau et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The potential pharmacological use of leptin to improve or reduce the impact on obese male fertility has been already suggested and although their potential use in clinical practice is promising, the data are still limited and need further confirmation (Alves et al ., ). Interestingly, previous studies suggested also the potential clinical use of leptin as a biomarker in IVF cycles, considering that high serum and/or follicular fluid leptin concentrations have correlated negatively with cycle outcome (Catteau et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…OB‐R belongs to class I cytokine superfamily, and there are at least six different isoforms, named OB‐R a , OB‐R b , OB‐R c , OB‐R d , OB‐R e , OB‐R f . The six isoforms are divided into three categories: short (OB‐R a , OB‐R c , OB‐R d , OB‐R f ), long (OB‐R b ) and soluble (OB‐R e ) forms (Catteau et al., ; Wauman, Zabeau, & Tavernier, ). (Figure ) Different OB‐R activation conveys different biological activities of leptin.…”
Section: Structure and Expression Of Leptin And Leptin Receptormentioning
confidence: 99%
“…Leptin is an adipocyte hormone and is also called as the master hormone of the body which is produced mostly by adipocytes and by granulosa, theca cells and cumulus cells of ovarian follicles (Kamyabi and Gholamalizade, 2015;Catteau et al, 2016). It is a 16-kDa protein of 167 amino acids plays a crucial role in the regulation of energy balance and body weight control (Farhood et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Circulating leptin binds to leptin receptor and functions as part of a signalling pathway, including Janus kinase 2 (JAK2)-signal transducer and activator of transcription 3 (STAT3), insulin receptor substrate (IRS)-phosphatidylinositol 3-kinase (PI3K), mitogen-activated protein kinase (MAPK), and 5' adenosine monophosphate-activated protein kinase (AMPK)/ acetyl-CoA carboxylase (ACC). Among these, the JAS/STAT3 plays an important role in the regulation of energy homeostasis (Catteau et al, 2016). In human beings, leptin and leptin receptor genes are present at chromosomal locations 7q32.1 and 1p31.3 respectively.…”
Section: Introductionmentioning
confidence: 99%